Galaxy Zoo: The fundamentally different co-evolution of supermassive black holes and their early- and late-type host galaxies - Schawinski, K; Urry, C; Virani, S; Coppi, P; Bamford, S; Treister, E; Lintott, C; Sarzi, M; Keel, W; Kaviraj, S; Cardamone, C; Masters, K; et al. (Institute of Physics Publishing, 2010)
We use data from the Sloan Digital Sky Survey and visual classifications of morphology from the Galaxy Zoo project to study black hole growth in the nearby Universe (z < 0.05) and to break down the AGN host galaxy population by color, stellar mass and morphology. We find that black hole growth at luminosities L_OIII >1E40 erg/s in early- and late-type galaxies is fundamentally different. AGN host galaxies as a population have a broad range of stellar masses (1E10-1E11 Msun), reside in the green valley of the color-mass diagram and their central black holes have median masses around 1E6.5 Msun. However, by comparing early- and late-type AGN host galaxies to their non-active counterparts, we find several key differences: in early-type galaxies, it is preferentially the galaxies with the least massive black holes that are growing, while late-type galaxies, it is preferentially the most massive}black holes that are growing. The duty cycle of AGN in early-type galaxies is strongly peaked in the green valley below the low-mass end (1E10 Msun) of the red sequence at stellar masses where there is a steady supply of blue cloud progenitors. The duty cycle of AGN in late-type galaxies on the other hand peaks in massive (1E11 Msun) green and red late-types which generally do not have a corresponding blue cloud population of similar mass. At high Eddington ratios (L/L_Edd > 0.1), the only population with a substantial fraction of AGN are the low-mass green valley early-type galaxies. Finally, the Milky Way likely resides in the "sweet spot" on the color-mass diagram where the AGN duty cycle of late-type galaxies is highest. We discuss the implications of these results for our understanding of the role of AGN in the evolution of galaxies